2011
DOI: 10.1111/j.1365-2141.2011.08569.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of haematological parameters with bortezomib–melphalan–prednisone versus melphalan–prednisone in newly diagnosed myeloma, with evaluation of long‐term outcomes and risk of thromboembolic events with use of erythropoiesis‐stimulating agents: analysis of the VISTA trial

Abstract: SummaryAlthough haematological toxicities, such as anaemia, are common in multiple myeloma (MM), no clear consensus exists on the use and impact of erythropoiesis-stimulating agents (ESA) on outcomes in MM. This analysis characterizes haematological toxicities and associated interventions in the phase III VISTA (Velcade Ò as Initial Standard Therapy in Multiple Myeloma:Assessment with Melphalan and Prednisone) study of bortezomib plus melphalan/prednisone (VMP, n = 344) versus MP (n = 338) in previously untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, one randomized study (VISTA sub-analysis) showed no evidence of inferior outcome after ESA treatment, albeit patient numbers were very limited and, therefore, statistically under-powered. 43 The most recent guidelines from the American Society of Hematology (ASH) and American Society of Clinical Oncology (ASCO) recommend the administration of ESAs at the lowest possible dose to avoid transfusions. In case of iron deficiency, which is indicated by low transferrin satu-…”
Section: Regimens Neutropenia (%) Vte (%) Pn (%) Infection (%) Spm (%)mentioning
confidence: 99%
“…However, one randomized study (VISTA sub-analysis) showed no evidence of inferior outcome after ESA treatment, albeit patient numbers were very limited and, therefore, statistically under-powered. 43 The most recent guidelines from the American Society of Hematology (ASH) and American Society of Clinical Oncology (ASCO) recommend the administration of ESAs at the lowest possible dose to avoid transfusions. In case of iron deficiency, which is indicated by low transferrin satu-…”
Section: Regimens Neutropenia (%) Vte (%) Pn (%) Infection (%) Spm (%)mentioning
confidence: 99%
“…Moreover, the combined use of IMIDS with EPO might increase the risk of VTE 66 . On the other hand, it should be emphasized that proteasome inhibitors have been shown to be safe, even when combined with ESAs, as shown in the VISTA trial 21 .…”
Section: Discussionmentioning
confidence: 99%
“…We 6 7 11 17 and others 18 19 , have noted prolonged survival and improved immunological functions in MM mouse models and MM patients, linked to EPO administration. Notably, others reported contradicting data regarding rHuEPO treatment in MM patients 20 21 , which warrants further research to elucidate this question.…”
mentioning
confidence: 97%
“…A few randomized studies have evaluated the impact of ESAs on outcomes in patients with MM. One randomized study showed no evidence of inferior outcome following ESA treatment; however, the trial was small and statistically underpowered (Richardson et al, 2011). ɐ To minimize the risk of infection, the use of neutropenic precautions is recommended in patients with MM (see Figure 3).…”
Section: Level Of Evidence IImentioning
confidence: 99%